Non-clinical research – laboratory based. (November 2016) - Salji, Mark; Ahmad, Imran; Winchester, Catherine L
Venturing into the world of laboratory-based research can be an extremely rewarding but also daunting step for clinicians. Combining our everyday clinical practice with cutting-edge laboratory research bridges our understanding of the basis of disease processes, and we can play a key role in translating such knowledge into better treatment for patients. Here, we discuss some important factors to take into consideration before putting on your lab coat.